Cognitive Maps and Social Ecology in Young Adult Fiction (Based on a keynote address presented at the fifth national conference of the Shiraz University Centre for Research in Children's Literature Studies, Shiraz, Iran, May 2015). Issue 2 (December 2015) - Stephens, John
Abstract : The nexus of the conceptual domains of cognitive mapping and social ecology offers a constructive methodology for examining some aspects of Young Adult fiction, and in this article I explore what I see as the possibilities of this conjunction. On the one hand, social ecology (also referred to as ecocultural theory or the bioecological model) impacts upon representations of subjectivity within YA fiction, and on the other, the literal and metaphorical interpretations of space and place enabled by cognitive mapping function as a framework to structure discussion of the relationship between ecology and subjectivity. Because mapping is an activity performed both by characters within the text and through narrator–narratee transactions, it has a narrative function that mediates the core social ecology foci of proximal processes, characterisation, ecocultural orientation and the experience of temporality. Taking examples from Neil Gaiman's The Graveyard Book, David Almond's The Fire-Eaters and John Green's Paper Towns, the article explores some of the interactions between key cognitive and social processes and the narrative structures within which they are expressed.